Polysaccharide-based Edible Film Coatings for Preservation and Packaging of Food - Sanjaykumar, Gupta Swati; Malviya, Rishabha; Sundram, Sonali; Sridhar, Sathvik Belagodu; Singh, Deependra Pratap (Natural Products Journal, The, 2025)
A lot of interest has been shown in edible films and coatings made from homo- and heteropolysaccharides as environmentally friendly substitutes for food packaging and preservation. This review delves into the various uses, characteristics, and working principles that underpin these biopolymer-based materials' ability to prolong food products' shelf lives and preserve their quality. Clarified are the structure-function correlations of a variety of polysaccharides, such as starch, chitosan, cellulose, and their blends, emphasizing their potential as barrier coverings against microbial, oxygen, and moisture contamination. Additionally, the addition of bioactive substances and nanomaterials to these films is covered, with a focus on how these materials improve the films' mechanical, antioxidant, and antibacterial qualities. The paper also discusses future options for research and case studies of these biopolymer-based systems. All things considered, the application of edible films and coatings based on homo- and heteropolysaccharide biopolymers offers viable options for environmentally friendly food packaging that preserves food quality and safety while lowering environmental impact. The need for this review arises from the growing demand for sustainable, environment-friendly alternatives to traditional plastic packaging.
Keywords: Homo-polysaccharides